Characterizing the Quaternary Hydrostratigraphy of Buried Valleys using Multi-Parameter Borehole Geophysics, Georgetown, Ontario - Brennan, Andrew N. (My University, 2011)
In 2009, the Regional Municipality of Halton and McMaster University initiated a 2-year collaborative study (Georgetown Aquifer Characterization Study-GACS) of the groundwater resource potential of Quaternary sediments near Georgetown, Ontario. As part of that study, this thesis investigated the Quaternary infill stratigraphy of the Middle Sixteen Mile Creek (MSMC) and Cedarvale (CV) buried valley systems using newly acquired core and borehole geophysical data. Multi-parameter geophysical log suites (natural gamma, EM conductivity, resistivity, magnetic susceptibility, full-waveform sonic, caliper) were acquired in 16 new boreholes (16 m to 55 m depth), pre-existing monitoring wells and from archival data. Characteristic log responses (electrofacies) were identified and correlated with core to produce a detailed subsurface model of a 20-km2 area to the southwest of Georgetown. Nine distinctive lithostratgraphic units were identified and their geometry mapped across the study area as structure contour and isochore thickness maps. The subsurface model shows that the CV valley truncates the Late Wisconsin MSMC stratigraphy along a channelized erosional unconformity and is a younger (post-glacial?) sediment-hosted valley system. Model results demonstrate the high level of stratigraphic heterogeneity and complexity that is inherent in bedrock valley systems and provides a geological framework for understanding groundwater resource availability.
Principal component analysis (PCA) was applied to selected log suites to evaluate the potential for objective lithologic classification using log data. Gamma, resistivity and conductivity logs were most useful for lithologic typing, while p-wave velocity and resistivity logs were more diagnostic of compact diamict units. Cross plots of the first and second principal components of log parameters discriminated silts and clays/shales from sand/gravel and diamict lithofacies. The results show that PCA is a viable method for predicting subsurface lithology in un-cored boreholes and can assist in the identification of hydrostratigraphic units.
Keywords: borehole geophysics; buried bedrock valleys; Georgetown Ontario; principal component analysis; hydrostratigraphy; lithologic classification; Geophysics and Seismology; Geophysics and Seismology